Preparation method of nanocrystalline composite magnetic powder core

By forming a three-layer core-shell structure insulating layer on the nanocrystalline magnetic powder core, the problem of large losses in the existing soft magnetic powder core in high-frequency environments is solved, and the performance improvement of high resistivity and low loss is achieved.

CN119480319APending Publication Date: 2025-02-18NINGBO INNOVATION CENT FOR APPLIED MAGNETICS CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411636172.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing soft magnetic powder cores have large losses in high-frequency environments, and the thermal stability of organic insulating materials is poor, which limits the performance of the magnetic powder core.

Method used

Using nanocrystalline magnetic powder as the basic material, the first insulating layer is formed by the treatment of polyvinylpyrrolidone (PVP) dispersion and NH3·H2O, and then a second insulating layer is formed using acetone solution, and finally mixed with the resin to cure it to form three layers. Insulating layer of core-shell structure.

Benefits of technology

The resistivity of the nanocrystal composite magnetic powder core is significantly improved, effectively suppressing eddy current losses, and maintaining a high resistivity at high temperatures, improving the high-frequency magnetic permeability characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480319A_ABST
    Figure CN119480319A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a nanocrystalline composite magnetic powder core, which comprises the following steps: adding nanocrystalline magnetic powder into polyvinylpyrrolidone (PVP) dispersion liquid, and uniformly stirring to obtain a first mixed solution; dropwise adding NH3.H2O into the first mixed solution to obtain a second mixed solution, heating the second mixed solution to obtain powder, and washing and drying the powder to form a first insulating layer on the surface of the nanocrystalline magnetic powder; adding the nanocrystalline magnetic powder with the first insulating layer formed on the surface into an acid acetone solution, reacting under a water bath condition until acetone is completely volatilized, and then drying, so that the first insulating layer and a second insulating layer are formed on the surface of the nanocrystalline magnetic powder; and the nanocrystalline magnetic powder with the first insulating layer and the second insulating layer formed on the surface is mixed with resin, and drying, cold pressing and curing are performed to obtain the nanocrystalline composite magnetic powder core. The nanocrystalline composite magnetic powder core prepared through the preparation method has high resistivity, and eddy current loss is effectively inhibited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of magnetic materials, and in particular relates to a method for preparing a nanocrystalline composite magnetic powder core. Background Art

[0002] With the advent of the 5G era, the rapid development of semiconductor technology has put forward higher requirements for the miniaturization, high frequency and high power density of electronic devices. However, almost no soft magnetic materials can meet the external environment requirements of the third-generation wide bandgap semiconductors, which further restricts the development of the next generation of electronic devices.

[0003] Soft magnetic powder core is a composite material composed of magnetic particles, insulating medium and randomly distributed dispersed air gaps. It has the advantages of high saturation magnetization, good frequency characteristics, high DC bias characteristics, high Curie temperature, etc. It is widely used in inductors such as reactors, transformers, choke coils, etc. As electronic components develop towards miniaturization, high frequency and low loss, its basic component unit is fine magnetic particles coated with insulation, which can effectively isolate the eddy current between particles. At the same time, the surface of the fine-sized magnetic particle matrix has almost no skin effect, and the high-frequency stability is good. It can be widely used in electronic components such as switching power supplies, PFC power supplies, and high-frequency inverters. With the development of the electronics industry, electronic products tend to be miniaturized, and the requirements for the performance of magnetic powder cores are also increasing. As a member of the soft magnetic powder core family, nanocrystalline composite magnetic powder core has comprehensive excellent magnetic properties such as high resistivity, high magnetic permeability, high quality factor, and low loss.

[0004] In order to improve the performance of nanocrystalline composite magnetic powder cores and reduce high-frequency losses, it is necessary to coat the surface of the magnetic powder with an insulating layer with high resistivity and good adhesion.

[0005] The invention patent application with publication number CN1224899A discloses a composite magnetic body, which uses organic substances such as epoxy resin and phenolic resin as insulating media between magnetic powders. However, during the organic insulation coating process, problems such as uneven coating, easy agglomeration, and poor bonding strength are prone to occur. In addition, since these organic insulating agents have poor heat resistance, the heat treatment temperature of the magnetic powder core is limited, resulting in poor performance of the magnetic powder core.

[0006] At present, inorganic materials are often used as insulating coating layers to form dense and uniform coating films. The invention patent application with publication number CN116417234A discloses a low-loss soft magnetic powder and a preparation method thereof, as well as a soft magnetic powder core. The preparation method comprises the following steps: step S1, pickling the metal soft magnetic powder to obtain pickled magnetic powder; step S2, depositing a metal oxide layer or a non-metal oxide layer on the surface of the pickled magnetic powder by magnetron sputtering, and then performing vacuum heat treatment to obtain a low-loss soft magnetic powder. The present invention applies the magnetron sputtering process to the coating preparation process of the soft magnetic powder, effectively improves the surface resistance of the soft magnetic powder by a relatively simple process, and prepares a low-loss soft magnetic powder that can be used at high frequencies. The soft magnetic powder core prepared by the invention also has low-loss performance at high frequencies. The magnetic powder core disclosed in the patent can effectively suppress high-frequency eddy current loss and improve the quality factor of the inductor device. However, since the reaction rate is difficult to control, the insulating layer is prone to expansion and cracking, which eventually leads to poor insulation. Summary of the invention

[0007] The invention provides a method for preparing a nanocrystalline composite magnetic powder core. The nanocrystalline composite magnetic powder core prepared by the preparation method has a higher resistivity and effectively suppresses eddy current loss.

[0008] The present invention provides a method for preparing a nanocrystalline composite magnetic powder core, comprising:

[0009] (1) adding nanocrystalline magnetic powder into a polyvinyl pyrrolidone (PVP) dispersion and stirring to obtain a first mixed solution;

[0010] (2) Add NH 3 ·H 2 O to obtain a second mixed solution, heat the second mixed solution in a reaction kettle to obtain powder, wash and dry the powder, so that a first insulating layer is formed on the surface of the nanocrystalline magnetic powder;

[0011] (3) adding the nanocrystalline magnetic powder with the first insulating layer formed on the surface to an acid acetone solution, reacting in a water bath until the acetone is completely volatilized, and then drying, so that the first insulating layer and the second insulating layer are formed on the surface of the nanocrystalline magnetic powder;

[0012] (4) The nanocrystalline magnetic powder with the first insulating layer and the second insulating layer formed on the surface is mixed with resin, dried, cold pressed, and solidified to obtain a nanocrystalline composite magnetic powder core.

[0013] Fe 3 O 4 Insulation coating, that is, the nanocrystalline magnetic powder particles after the first insulation layer coating have good dispersion, which solves the problem of easy agglomeration and poor coating effect during the organic coating process, thereby greatly improving the resistivity of the composite amorphous magnetic powder, effectively reducing the magnetic powder core loss, and at the same time improving its high-frequency magnetic permeability characteristics.

[0014] The present invention uses acid and resin for secondary and tertiary insulation coating. During the heat treatment process, even if the organic insulating material is decomposed by heat, the first insulating layer Fe 3 O 4 The existence of can still provide insulation protection for the magnetic powder particles, thus effectively avoiding the problems of reduced performance of the magnetic powder core and increased high-frequency loss caused by the low thermal stability of organic insulating materials.

[0015] Compared with directly coating the magnetic powder surface with resin material, and directly coating the magnetic powder surface with a mixed material of inorganic oxide and resin material, the three-time insulation coating method of the present invention can reduce the loss of the magnetic powder core and improve its effective magnetic permeability.

[0016] The present invention can control the three-layer core-shell structure insulating layer Fe by changing the amount of one or more of the precipitant ammonia water, high temperature reaction temperature and time, acid, water bath reaction temperature and time, resin, and nanocrystalline magnetic powder. 3 O 4 The thickness of @AL@EP can be adjusted to achieve different thickness of insulation coating effects, further regulating the performance of the nanocrystalline composite magnetic powder core, with flexible design and easy control.

[0017] Preferably, the NH 3 ·H 2 The concentration of O is 10-25wt.%, and the nanocrystalline magnetic powder is mixed with NH 3 ·H 2 The mass ratio of O is 4:1-10:1.

[0018] The present invention controls NH 3 ·H 2 O concentration and ratio to provide sufficient hydroxide ions to react with the iron ions in the nanocrystalline magnetic powder and avoid excessive ammonia concentration and amount of ammonia causing Fe 3 O 4 The insulating layer of nanocrystalline particles becomes thicker.

[0019] Preferably, the heating temperature in step (1) is 100-200° C., and the insulation time is 0.5-5 h.

[0020] The present invention controls the heating temperature and the holding time to provide sufficient energy to react on the surface of the nanocrystalline magnetic powder to obtain Fe 3 O 4 Nano-scale particles form the first insulating layer.

[0021] Preferably, the concentration of the acid in the acid acetone solution is 0.1%-0.5%, and the mass ratio of the nanocrystalline magnetic powder with the first insulating layer formed on the surface to the acid acetone solution is 3:2-3:5.

[0022] The present invention controls the concentration of the acid and the amount of the acid acetone solution so that the exposed nanocrystalline magnetic powder and part of the Fe 3 O 4 The particles react with an appropriate amount of acid to form a dense metal salt, that is, to form a second insulating layer. The nanocrystalline magnetic powder is wrapped by the first insulating layer and the second insulating layer to improve the resistivity, and the second insulating layer is prevented from being scaly so as to be prone to cracking, resulting in the matrix being exposed and the nanocrystalline magnetic powder being punctured.

[0023] Further preferably, the acid in the acid acetone solution is one of phosphoric acid, hydrochloric acid and nitric acid.

[0024] Preferably, the water bath conditions are: water bath temperature is 40-50° C., and reaction time is 1-4 h.

[0025] Preferably, the content of the resin in the nanocrystalline composite magnetic powder core is 1-2 wt.%.

[0026] The outermost layer of the nanocrystalline magnetic powder provided by the present invention is wrapped with an appropriate amount of resin to improve the resistivity and reduce the loss. Too much resin will further improve the resistivity of the composite nanocrystalline magnetic powder, but at the same time will introduce a large amount of non-magnetic material to cause magnetic dilution, thereby seriously sacrificing part of the comprehensive magnetic properties.

[0027] Preferably, the content of polyvinyl pyrrolidone (PVP) is controlled between 0.2-0.5 wt.%.

[0028] Preferably, in step (1), the stirring time is 0.5-2 h, and the stirring temperature is 30-50° C.

[0029] The invention controls the content, stirring time and temperature of the vinyl pyrrolidone (PVP) dispersion liquid to make the nanocrystalline magnetic powder particles evenly separated and modify the surface so that the surface can react with alkaline solution and acid solution to form an insulating layer.

[0030] Preferably, in step (2), the powder is washed 3-5 times and dried under vacuum conditions at 60-80° C. for 2-4 hours.

[0031] Preferably, in step (3), the drying temperature is 60-80° C. and the drying time is 0.5-2 h.

[0032] Preferably, in step (4), the drying temperature is 60-80° C. and the drying time is 0.5-2 h.

[0033] Preferably, in step (4), the cold pressing pressure is 400-800 MPa. The nanocrystalline composite magnetic powder core obtained under this pressure has an outer diameter of 14-20.3 mm and an inner diameter of 8-12.7 mm. The typical size specifications of the magnetic ring mold for preparing the composite nanocrystalline magnetic powder core sample are two: specification 1 with an outer diameter of 14 mm and an inner diameter of 8 mm; specification 2 with an outer diameter of 20.3 mm and an inner diameter of 12.7 mm.

[0034] Preferably, in step (4), the temperature for curing treatment is 150-250°C.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] The present invention adds NH 3 ·H 2 O, through heating reaction, Fe is formed on the surface of nanocrystalline magnetic powder 3 O 4 The particles are the first insulating layer, but since the first insulating layer is relatively sparse, the present invention uses an acid acetone solution in a water bath to allow the acid to react with the exposed magnetic powder and part of the Fe 3 O 4 The particles react to form a dense insulating layer, that is, through the first insulating layer and the second insulating layer, the resistivity is improved, and even at high temperatures, the resistivity can be high, effectively suppressing eddy current loss.

[0037] The present invention utilizes resin to make the outermost layer of nanocrystalline magnetic powder denser, and improves uniformity and adhesion, plays a good bonding and sealing role on the surface of composite nanocrystalline magnetic powder, and has higher resistivity at lower temperatures. Due to the first insulating layer and the second insulating layer, the present invention enables the nanocrystalline composite magnetic powder core to have a higher resistivity even at a higher temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 The nanocrystalline composite magnetic powder and the magnetic powder core deposited with the first insulating layer and the second insulating layer provided in Example 1 of the present invention, wherein: Figure 1 a shows that NC@Fe 3 O 4 @AL@EP is a nanoparticle first insulating layer Fe 3 O 4 , nanocrystalline composite magnetic powder morphology of the acid salt second insulating layer AL and the resin third insulating layer EP; Figure 1 b shows that NC@Fe 3 O 4 @AL is the first insulating layer with nanoparticles Fe 3 O 4 Magnetic powder morphology of the second insulating layer AL of the acid salt;

[0039] like Figure 2 The nanocrystalline composite magnetic powder and the magnetic powder core deposited with the first insulating layer and the second insulating layer provided in Example 2 of the present invention, wherein: Figure 2 a shows that NC@Fe 3 O 4 @AL@EP is a nanoparticle first insulating layer Fe 3 O 4 , nanocrystalline composite magnetic powder morphology of the acid salt second insulating layer AL and the resin third insulating layer EP; Figure 2 b shows that NC@Fe 3 O 4 @AL is the first insulating layer with nanoparticles Fe 3 O 4 The morphology of nanocrystalline composite magnetic powder of the second insulating layer AL of the acid salt;

[0040] like Figure 3 As shown, the morphology of the first insulating layer and the resin insulating layer deposited on the magnetic powder core provided in Comparative Example 1 of the present invention and the morphology of the first insulating layer deposited, Figure 3 a shows that NC@Fe 3 O 4 @EP is the first insulating layer with nanoparticles Fe 3 O 4 The morphology of nanocrystalline composite magnetic powder with resin insulation layer EP; Figure 3 b shows that NC@Fe 3 O 4 The first insulating layer of Fe nanoparticles 3 O 4 The morphology of nanocrystalline composite magnetic powder;

[0041] like Figure 4 As shown, the morphology of the second insulating layer and the resin insulating layer deposited on the magnetic powder core and the morphology of the second insulating layer deposited are provided in Comparative Example 2 of the present invention. Figure 4 a shows that NC@AL@EP is a nanocrystalline composite magnetic powder morphology image having an acid salt second insulating layer AL and a resin insulating layer EP; Figure 4 b shows that NC@AL is a morphology of nanocrystalline composite magnetic powder with an acid salt insulating layer AL;

[0042] like Figure 5 As shown, the morphology of the resin insulation layer deposited on the magnetic powder core and the morphology of the bare magnetic powder core provided in Comparative Example 3 of the present invention are shown in FIG. Figure 5 a shows that NC@EP is a morphology of nanocrystalline composite magnetic powder with a resin insulating layer EP; Figure 5 b shows the morphology of NC, which is a nanocrystalline bare magnetic powder without any treatment. DETAILED DESCRIPTION

[0043] The present invention is further described in detail below in conjunction with the embodiments and drawings. It should be pointed out that the embodiments described below are intended to facilitate the understanding of the present invention and do not have any limiting effect on the present invention.

[0044] Example 1

[0045] This embodiment provides a method for preparing a nanocrystalline composite magnetic powder core, comprising:

[0046] (1) Dispersion preparation:

[0047] 0.5 wt.% PVP was added into deionized water to prepare a dispersion;

[0048] (2) Surface modification:

[0049] Add the nanocrystalline magnetic powder to the 45°C PVP dispersion obtained in step (1) and stir evenly for 0.5h to obtain surface-modified nanocrystalline magnetic powder;

[0050] (3) Design of the first insulation layer:

[0051] Add 25wt.% NH 3 ·H 2 O is dripped into the surface-modified nanocrystalline magnetic powder mixed solution obtained in step (2). Subsequently, NH 3 ·H 2 The mixed solution of nanocrystalline magnetic powder of O was placed in a high-temperature reactor at 150°C and kept warm for 1 hour. The powder was washed with deionized water for 3 times and then dried in a vacuum drying oven at 50°C for 2 hours.

[0052] (4) Design of the second insulation layer:

[0053] The nanocrystalline magnetic powder with the first insulating layer obtained in step (3) was mixed with a 0.2 wt.% phosphate acetone solution, reacted in a 50°C water bath for 1 h until the acetone was completely volatilized, and dried in a 50°C vacuum drying oven for 2 h. The morphology was as follows: Figure 1 As shown in b.

[0054] (5) Design of the third insulation layer:

[0055] The nanocrystalline magnetic powder with the first and second insulating layers obtained in step (4) is mixed with a resin having a content of 2 wt.%, and dried in a vacuum drying oven at 50° C. for 2 h to improve the uniformity and adhesion of the insulating layer.

[0056] (6) Molding process:

[0057] Then, the nanocrystalline composite magnetic powder obtained in step (5) was pressed into a nanocrystalline composite magnetic powder core with an outer diameter of 20.3 mm and an inner diameter of 12.7 mm by cold pressing at a pressure of 600 MPa.

[0058] (7) Curing treatment:

[0059] Finally, the nanocrystalline composite magnetic powder core obtained in step (6) was cured at 200°C and the magnetic powder core was tested. Figure 1 As shown in a.

[0060] The properties of the nanocrystalline composite magnetic powder core prepared in this embodiment are shown in Table 1.

[0061] Table 1 Performance parameters of the nanocrystalline composite magnetic powder core obtained in Example 1

[0062]

[0063] Example 2

[0064] This embodiment provides a method for preparing a nanocrystalline composite magnetic powder core, comprising:

[0065] (1) Dispersion preparation:

[0066] 0.3 wt.% PVP was added into deionized water to prepare a dispersion;

[0067] (2) Surface modification:

[0068] Add the nanocrystalline magnetic powder to the 50°C PVP dispersion obtained in step (1) and stir evenly for 0.5h to obtain surface-modified nanocrystalline magnetic powder;

[0069] (3) Design of the first insulation layer:

[0070] Add 20 wt.% NH 3 ·H 2 O is dripped into the surface-modified nanocrystalline magnetic powder mixed solution obtained in step (2). Subsequently, NH 3 ·H 2 The mixed solution of nanocrystalline magnetic powder of O was placed in a high-temperature reactor at 100°C and kept warm for 2 hours. The powder was washed three times with deionized water and then dried in a vacuum drying oven at 50°C for 2 hours.

[0071] (4) Design of the second insulation layer:

[0072] The nanocrystalline magnetic powder with the first insulating layer obtained in step (3) was mixed with a 0.3 wt.% phosphate acetone solution, reacted in a 50°C water bath for 1 h until the acetone was completely volatilized, and dried in a 50°C vacuum drying oven for 2 h. The morphology was as follows: Figure 2 As shown in b.

[0073] (5) Design of the third insulation layer:

[0074] The nanocrystalline magnetic powder with the first and second insulating layers obtained in step (4) is mixed with a resin having a content of 2 wt.%, and dried in a vacuum drying oven at 50° C. for 2 h to improve the uniformity and adhesion of the insulating layer.

[0075] (6) Molding process:

[0076] Then, the nanocrystalline composite magnetic powder obtained in step (5) was pressed into a nanocrystalline composite magnetic powder core with an outer diameter of 20.3 mm and an inner diameter of 12.7 mm by cold pressing at a pressure of 600 MPa.

[0077] (7) Curing treatment:

[0078] Finally, the nanocrystalline composite magnetic powder core obtained in step (6) was cured at 200°C and the magnetic powder core was tested. Figure 2 As shown in a.

[0079] The properties of the nanocrystalline composite magnetic powder core prepared in this example are shown in Table 2.

[0080] Table 2 Performance parameters of the nanocrystalline composite magnetic powder core obtained in Example 2

[0081]

[0082] Comparative Example 1

[0083] The preparation method of the nanocrystalline composite magnetic powder core provided in this comparative example comprises:

[0084] (1) Dispersion preparation:

[0085] 0.4 wt.% PVP was added into deionized water to prepare a dispersion;

[0086] (2) Surface modification:

[0087] Add the nanocrystalline magnetic powder to the 50°C PVP dispersion obtained in step (1) and stir evenly for 0.5h to obtain surface-modified nanocrystalline magnetic powder;

[0088] (3) Design of the first insulation layer:

[0089] Add 25wt.% NH 3 ·H 2 O is dripped into the surface-modified nanocrystalline magnetic powder mixed solution obtained in step (2). Subsequently, NH 3 ·H 2 The mixed solution of nanocrystalline magnetic powder of O was placed in a high-temperature reactor at 150°C and kept warm for 1 hour. The powder was washed with deionized water 5 times and then dried in a vacuum oven at 50°C for 2 hours. The morphology was as follows: Figure 3 As shown in b.

[0090] (4) Design of the second insulation layer:

[0091] The nanocrystalline magnetic powder with the first insulating layer obtained in step (3) is mixed with a resin with a content of 2 wt.%, and dried in a vacuum drying oven at 50°C for 2 hours to improve the uniformity and adhesion of the insulating layer. The morphology is as follows: Figure 3 As shown in a.

[0092] (5) Molding process:

[0093] Then, the nanocrystalline composite magnetic powder obtained in step (4) was pressed into a nanocrystalline composite magnetic powder core with an outer diameter of 20.3 mm and an inner diameter of 12.7 mm by cold pressing at a pressure of 600 MPa.

[0094] (6) Curing treatment:

[0095] Finally, the nanocrystalline composite magnetic powder core obtained in step (5) is cured at 200° C. and the magnetic powder core is tested.

[0096] The properties of the nanocrystalline composite magnetic powder core prepared in this comparative example are shown in Table 4.

[0097] Table 3 Performance parameters of the nanocrystalline composite magnetic powder core prepared in Comparative Example 1

[0098]

[0099] Comparative Example 2

[0100] The preparation method of the nanocrystalline composite magnetic powder core provided in this comparative example comprises:

[0101] (1) Dispersion preparation:

[0102] 0.5 wt.% PVP was added into deionized water to prepare a dispersion;

[0103] (2) Surface modification:

[0104] Add the nanocrystalline magnetic powder to the 45°C PVP dispersion obtained in step (1) and stir evenly for 0.5h to obtain surface-modified nanocrystalline magnetic powder;

[0105] (3) Design of the first insulation layer:

[0106] The nanocrystalline magnetic powder obtained in step (2) was mixed with a 0.2 wt.% phosphate acetone solution, reacted in a 50°C water bath for 1 h until the acetone was completely volatilized, and dried in a 50°C vacuum drying oven for 2 h. The morphology was as follows: Figure 4 As shown in b.

[0107] (4) Design of the second insulation layer:

[0108] The nanocrystalline magnetic powder with the first insulating layer obtained in step (3) was mixed with a 2 wt.% resin and dried in a vacuum drying oven at 50° C. for 2 h to improve the uniformity and adhesion of the insulating layer. The morphology was as follows: Figure 4 As shown in a.

[0109] (5) Molding process:

[0110] Then, the nanocrystalline composite magnetic powder obtained in step (4) was pressed into a nanocrystalline composite magnetic powder core with an outer diameter of 20.3 mm and an inner diameter of 12.7 mm by cold pressing at a pressure of 600 MPa.

[0111] (6) Curing treatment:

[0112] Finally, the nanocrystalline composite magnetic powder core obtained in step (5) is cured at 200° C. and the magnetic powder core is tested.

[0113] The properties of the nanocrystalline composite magnetic powder core prepared in this comparative example are shown in Table 4.

[0114] Table 4 Performance parameters of the nanocrystalline composite magnetic powder core prepared in Comparative Example 2

[0115]

[0116] Comparative Example 3

[0117] The preparation method of the nanocrystalline composite magnetic powder core provided in this comparative example comprises:

[0118] (1) Dispersion preparation:

[0119] 0.5 wt.% PVP was added into deionized water to prepare a dispersion;

[0120] (2) Surface modification:

[0121] Add the nanocrystalline magnetic powder to the 45°C PVP dispersion obtained in step (1) and stir evenly for 0.5h to obtain surface-modified nanocrystalline magnetic powder;

[0122] (3) Design of the first insulation layer:

[0123] The nanocrystalline magnetic powder obtained in step (2) was mixed with 2 wt.% of resin and dried in a vacuum drying oven at 50°C for 2 h to improve the uniformity and adhesion of the insulating layer. The morphology was as follows: Figure 5 As shown in b.

[0124] (4) Molding process:

[0125] Then, the nanocrystalline composite magnetic powder obtained in step (3) was pressed into a nanocrystalline composite magnetic powder core with an outer diameter of 20.3 mm and an inner diameter of 12.7 mm by cold pressing at a pressure of 600 MPa.

[0126] (5) Curing treatment:

[0127] Finally, the nanocrystalline composite magnetic powder core obtained in step (4) was cured at 200°C and the magnetic powder core was tested. Figure 5 As shown in a.

[0128] The properties of the nanocrystalline composite magnetic powder core prepared in this comparative example are shown in Table 5.

[0129] Table 5 Performance parameters of the nanocrystalline composite magnetic powder core obtained in Comparative Example 3

[0130]

[0131] It can be seen from Tables 1 and 2 that the nanocrystalline composite magnetic powder core prepared in the embodiments of the present invention has lower loss and higher DC bias.

[0132] like Figure 1 As shown, Example 1, Figure 1 a shows that NC@Fe 3 O 4 @AL@EP is a nanoparticle first insulating layer Fe 3 O 4 , nanocrystalline composite magnetic powder morphology of the acid salt second insulating layer AL and the resin third insulating layer EP; Figure 1 b shows that NC@Fe 3 O 4 @AL is the first insulating layer with nanoparticles Fe 3 O 4 The morphology of nanocrystalline composite magnetic powder of the second insulating layer AL of the acid salt;

[0133] like Figure 2 As shown in Example 2, Figure 2 a shows that NC@Fe 3 O 4 @AL@EP is a nanoparticle first insulating layer Fe 3 O 4 , nanocrystalline composite magnetic powder morphology of the acid salt second insulating layer AL and the resin third insulating layer EP; Figure 2 b shows that NC@Fe 3 O 4 @AL is the first insulating layer with nanoparticles Fe 3 O 4 The morphology of nanocrystalline composite magnetic powder of the second insulating layer AL of the acid salt;

[0134] like Figure 3 As shown, comparative example 1, Figure 3 a shows that NC@Fe 3 O 4@EP is the first insulating layer with nanoparticles Fe 3 O 4 The morphology of nanocrystalline composite magnetic powder with resin insulation layer EP; Figure 3 b shows that NC@Fe 3 O 4 The first insulating layer of Fe nanoparticles 3 O 4 The morphology of nanocrystalline composite magnetic powder;

[0135] like Figure 4 As shown, comparative example 2, Figure 4 a shows that NC@AL@EP is a nanocrystalline composite magnetic powder morphology image having an acid salt second insulating layer AL and a resin insulating layer EP; Figure 4 b shows that NC@AL is a morphology of nanocrystalline composite magnetic powder with an acid salt insulating layer AL;

[0136] like Figure 5 As shown, comparative example 3, Figure 5 a shows that NC@EP is a morphology of nanocrystalline composite magnetic powder with a resin insulating layer EP; Figure 5 b shows the morphology of NC, which is a nanocrystalline bare magnetic powder without any treatment.

[0137] The embodiments described above provide a detailed description of the technical solutions of the present invention. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, supplements or similar substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a nanocrystalline composite magnetic powder core, characterized in that: include: (1) adding nanocrystalline magnetic powder into a polyvinyl pyrrolidone dispersion and stirring the mixture to obtain a first mixed solution; (2) adding NH3·H2O dropwise to the first mixed solution to obtain a second mixed solution, heating the second mixed solution in a reaction kettle to obtain a powder, and washing and drying the powder to form a first insulating layer on the surface of the nanocrystalline magnetic powder; (3) adding the nanocrystalline magnetic powder with the first insulating layer formed on the surface to an acid acetone solution, reacting in a water bath until the acetone is completely volatilized, and then drying, so that the first insulating layer and the second insulating layer are formed on the surface of the nanocrystalline magnetic powder; (4) The nanocrystalline magnetic powder with the first insulating layer and the second insulating layer formed on the surface is mixed with resin, dried, cold pressed, and solidified to obtain a nanocrystalline composite magnetic powder core.

2. The method for preparing the nanocrystalline composite magnetic powder core according to claim 1, characterized in that: The concentration of the NH3·H2O is 10-25wt.%, and the mass ratio of the nanocrystalline magnetic powder to NH3·H2O is 4:1-10:

1.

3. The method for preparing the nanocrystalline composite magnetic powder core according to claim 1, characterized in that: The heating temperature of step (2) is 100-200° C., and the insulation time is 0.5-5 h.

4. The method for preparing a nanocrystalline composite magnetic powder core according to claim 1, characterized in that: The concentration of acid in the acid acetone solution is 0.1%-0.5%, and the mass ratio of the nanocrystalline magnetic powder with the first insulating layer formed on the surface to the acid acetone solution is 3:2-3:

5.

5. The method for preparing the nanocrystalline composite magnetic powder core according to claim 4, characterized in that: The acid in the acid acetone solution is one of phosphoric acid, hydrochloric acid and nitric acid.

6. The method for preparing a nanocrystalline composite magnetic powder core according to claim 1, characterized in that: The water bath conditions are: water bath temperature is 40-50° C., and reaction time is 1-4 h.

7. The method for preparing a nanocrystalline composite magnetic powder core according to claim 1, characterized in that: The content of the resin in the nanocrystalline composite magnetic powder core is 1-2 wt.%.

8. The method for preparing a nanocrystalline composite magnetic powder core according to claim 1, characterized in that: The content of polyvinyl pyrrolidone is 0.2-0.5wt.%.

9. The method for preparing a nanocrystalline composite magnetic powder core according to claim 1, characterized in that: In step (1), the stirring time is 0.5-2h, and the stirring temperature is 30-50°C.

10. The method for preparing a nanocrystalline composite magnetic powder core according to claim 1, characterized in that: In step (4), the cold pressing pressure is 400-800 MPa.

Citation Information

Patent Citations

  • Low-loss soft magnetic powder, preparation method thereof and soft magnetic powder core

    CN116417234A

  • Built-up magnet, its producing method and Fe-Al-Si soft magnetic alloy powder used therefor

    CN1224899A